The Influence of the Qur'an Hadith Learning Model Based on Reflective Qur'anic Inquiry to Improve Islamic Literacy and Social Awareness of Madrasah Aliyah Students - Saddang, Muhammad; Zuhdiah, Zuhdiah; Umri, Umri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aimed to examine the influence of the Reflective Qur’anic Inquiry-based Al-Qur’an Hadith learning model on improving students’ Islamic literacy and social awareness at MAN 1 Majene. The research applied a quantitative method with both descriptive and inferential approaches to examine the influence of the Reflective Qur’anic Inquiry learning model on the Islamic literacy and social awareness of eleventh-class students during the 2024/2025 academic year. The study population consisted of 396 students from 15 classes, while the sample included 80 students selected through a simple random sampling technique using the Taro Yamane formula. Data collection was conducted through documentation and a Likert-scale questionnaire that had previously undergone validity and reliability testing. The collected data were analyzed using SPSS version 26 through descriptive statistical analysis, prerequisite testing such as normality and linearity tests, and hypothesis testing using simple linear regression, coefficient of determination analysis, and the F-test to determine both the influence and feasibility of the regression model used in the study. The findings revealed that the implementation of the Reflective Qur’anic Inquiry-based Al-Qur’an Hadith learning model at MAN 1 Majene was categorized as fairly good and contributed to improving students’ Islamic literacy and social awareness. In addition, the hypothesis testing demonstrated that the learning model had a significant effect on increasing the Islamic literacy and social awareness of eleventh-class students. Therefore, the reflection- and inquiry-oriented learning model can be considered effective in helping students understand Islamic values while also fostering social awareness in their daily lives.